2022
DOI: 10.3390/cancers14092092
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Recurrence in Young Adult Cancer Patients—A Network Analysis

Abstract: Due to the high survival rates of many young cancer patients and a high risk of second tumors, fear of cancer recurrence (FCR) can cause serious impairment for adolescent and young adult (AYA) cancer patients. The aim of this study is to analyze the structure of the Fear of Disease Progression Questionnaire (FoP-Q-12) to better understand the construct of FCR. We performed a cross-sectional survey on a sample of AYA patients aged 15–39 years with different tumor entities. FCR was measured using the FoP-Q-12, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 71 publications
1
10
1
Order By: Relevance
“…An interesting cluster that emerged was the worriment cluster, which consisted of negative health outlook, health distress, symptom awareness, social isolation, worried about family getting cancer, and people treating you differently. Although our questions regarding worries were different, one other network analysis on AYAs focused on the construct of fear of cancer recurrence [ 47 ]. Here, the researchers found fear of serious medical interventions as the most central symptom in their network, with the highest node strengths for fear of pain, fear of relying on strangers for activities of daily living, and fear of severe medical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting cluster that emerged was the worriment cluster, which consisted of negative health outlook, health distress, symptom awareness, social isolation, worried about family getting cancer, and people treating you differently. Although our questions regarding worries were different, one other network analysis on AYAs focused on the construct of fear of cancer recurrence [ 47 ]. Here, the researchers found fear of serious medical interventions as the most central symptom in their network, with the highest node strengths for fear of pain, fear of relying on strangers for activities of daily living, and fear of severe medical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients diagnosed with cancer experience uncertainty and fear about the future. In particular, young cancer patients have a high fear of cancer recurrence due to low survival rates and a high risk of secondary cancers [ 34 ]. In a study of 247 adolescents and young adults, the majority reported high levels of fear of progression.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, young cancer patients have a high fear of cancer recurrence due to low survival rates and a high risk of secondary cancers. 34 In a study of 247 adolescents and young adults, the majority reported high levels of fear of progression. Consistent with previous research, 31,32 young age was identified as a predictor of fear of cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The available scientific literature relating to other types of cancer (e.g., breast cancer) suggests that fear seems to be the main reason why patients decline to participate in cancer screening programmes and periodic check-up appointments. Notwithstanding the numerous studies on this topic, the evidence is still limited ( Mohan et al, 2021 ; Muñoz-Sanz et al, 2021 ; Taylan et al, 2021 ; Richter et al, 2022 ). It is widely agreed by many health professionals that fear is a fundamental emotion in the array of human reactions, which can be understood as a defence mechanism; this, therefore, protects the healthy individual, which in turn is indispensable for survival.…”
Section: Discussionmentioning
confidence: 99%